Composite wafer and method for manufacturing composite wafer

JP2026170798APending Publication Date: 2026-10-22KOIKE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025064600
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0015】 本発明の各視点によれば、異なる方位のタンタル酸リチウム単結晶ウェーハ(LT)同士を接合した場合においても、あるいは異なる方位のニオブ酸リチウム単結晶ウェーハ(LN)同士を接合した場合においても、剥離することなく十分な接合強度を有する、複合ウェーハおよび複合ウェーハの製造方法を得ることができる。 このように、タンタル酸リチウム単結晶ウェーハ(LT)同士、またはニオブ酸リチウム単結晶ウェーハ(LN)同士の剥離が抑制され、これら複合ウェーハを表面弾性波(SAW)デバイスに用いた場合には、所望の性能を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170798000001_ABST
    Figure 2026170798000001_ABST
Patent Text Reader

Abstract

To provide a composite wafer with spurious emission reduction effects, and a method for manufacturing a composite wafer, which involves bonding lithium tantalate single crystal wafers or lithium niobate single crystal wafers together, and including the bonding structure. [Solution] In a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystals of different orientations are stacked, the thickness of the incomplete single crystal layer containing amorphous material formed at the bonding interface of the lithium tantalate single crystals or lithium niobate single crystals is 4 nm to 5 nm. This composite wafer can be obtained by the steps of forming lithium tantalate single crystals or lithium niobate single crystals of different orientations, bonding the formed lithium tantalate single crystals or lithium niobate single crystals of different orientations at room temperature, and further, after the room temperature bonding step, undergoing a heat treatment step of 250°C or lower.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a composite wafer and a method for manufacturing a composite wafer, and more particularly to a composite wafer and a method for manufacturing a composite wafer that suppresses delamination between bonded lithium tantalate single crystals or lithium niobate single crystals formed on the composite wafer. [Background technology]

[0002] Common piezoelectric materials such as lithium tantalate and lithium niobate are widely used as materials for surface acoustic wave (SAW) devices. Composite substrates (composite wafers) are manufactured by bonding a material with a low coefficient of thermal expansion to lithium tantalate or lithium niobate, and then thinning the lithium tantalate or lithium niobate side to a thickness of several micrometers to tens of micrometers by grinding or other methods. For example, Non-Patent Document 1 and Patent Document 1 report that spurious emissions can be reduced in surface acoustic wave (SAW) devices using composite wafers formed by joining lithium tantalate single crystal wafers (LT) with different crystal orientations. Similarly, it has been reported that spurious emissions can be reduced in surface acoustic wave (SAW) devices using composite wafers formed by bonding lithium niobate single crystal wafers (LN) with different crystal orientations. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2024-67557 [Non-patent literature]

[0004] [Non-Patent Document 1] Naoto Hara et al 2023 Jpn. J. Appl. Phys. 62SJ1056 [Overview of the project] [Problems that the invention aims to solve]

[0005] Incidentally, when joining lithium tantalate single crystals (LT) with different crystal orientations, or when joining lithium niobate single crystals (LN) with different crystal orientations to manufacture the composite wafer described above, various joining methods may be applicable. Therefore, the inventors considered manufacturing the composite wafer using a room-temperature joining method. This room-temperature bonding method involves irradiating the bonding surface of two wafers with a high-speed atomic beam (FAB) under high vacuum to remove and activate surface-terminal atoms and molecules, and then bonding the two activated surfaces by bringing them into contact and applying pressure. When lithium tantalate single crystals (LT) or lithium niobate single crystals (LN) were joined together using such conventionally known room-temperature bonding methods, the inventors conducted an investigation and found that the bonding strength of the wafers was insufficient.

[0006] If the bonding strength of the wafer is insufficient, lithium tantalate single crystals (LT) or lithium niobate single crystals (LN) can delaminate from each other during the manufacturing process of the composite wafer or the surface acoustic wave (SAW) device. This not only prevents the desired surface acoustic wave (SAW) device performance from being obtained, but also makes it impossible to manufacture the composite wafer itself.

[0007] In view of the above-mentioned problems, the object of the present invention is to provide a composite wafer and a method for manufacturing a composite wafer that has sufficient bonding strength without delaminating lithium tantalate single crystal films (LT) of different orientations, or lithium niobate single crystal films (LN) without delaminating them. [Means for solving the problem]

[0008] To solve the above problems, the composite wafer of the present invention is a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystals of different orientations are stacked, characterized in that the thickness of the incomplete single crystal layer containing amorphous material formed at the bonding interface between the lithium tantalate single crystals or lithium niobate single crystals is 4 nm or more and 5 nm or less. The thickness of this amorphous, incomplete single-crystal layer is observed by cross-sectional TEM observation. Furthermore, an amorphous, incomplete single-crystal layer refers to a layer in which the lattice-like contrast characteristic of single crystals is incomplete in high-resolution cross-sectional TEM images at magnification of 2 million or more, and is a region in which diffraction spots and ring-shaped patterns are detected together in electron diffraction patterns.

[0009] Thus, in a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystals of different orientations are stacked, if an incomplete single crystal layer containing amorphous material is formed at the bonding interface between the lithium tantalate single crystals or lithium niobate single crystals with a thickness of 4 nm to 5 nm, the atoms near the interface are rearranged to be energetically stable. As a result, the residual stress at the bonding interface after room-temperature bonding is reduced, and sufficient bonding strength is obtained. Furthermore, delamination between lithium tantalate single crystal films (LT) or lithium niobate single crystal films (LN) is suppressed during the manufacturing process of the composite wafer or the manufacturing process of the surface acoustic wave (SAW) device, so that the desired surface acoustic wave (SAW) device performance can be obtained.

[0010] In this context, the composite wafer is preferably constructed by stacking lithium tantalate single crystals or lithium niobate single crystals of different orientations from the surface side, followed by an SiO2 layer, an amorphous Si layer, a polycrystalline Si layer, and a Si substrate. It is not sufficient that lithium tantalate single crystals or lithium niobate single crystals of different orientations are bonded to each other with sufficient strength; in addition to the absence of peeling, warpage, and wafer cracking, including the methods for thinning the lithium tantalate single crystal or lithium niobate single crystal and integrating it with other layers, performance as a SAW device, that is, improvement of temperature characteristics and reduction of spurious, are required.

[0011] Further, the method for producing a composite wafer of the present invention is a method for producing a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystals of different orientations are directly bonded, the method comprising: a step of preparing lithium tantalate single crystal or lithium niobate single crystal wafers or films of different orientations; a step of subjecting the prepared lithium tantalate single crystal or lithium niobate single crystal wafers or films of different orientations to room-temperature bonding; and further comprising a heat treatment step at 250°C or lower after the room-temperature bonding step. In particular, the present invention is characterized in that the lithium tantalate single crystals or lithium niobate single crystals of different orientations formed on the respective support wafers are subjected to room-temperature bonding, and then a heat treatment at 250°C or lower is further performed.

[0012] In this way, by performing the heat treatment at 250°C or lower after the room-temperature bonding of the lithium tantalate single crystal or lithium niobate single crystal wafers or films of different orientations, the bonding between the lithium tantalate single crystals or the lithium niobate single crystals of different orientations achieves sufficient bonding strength, peeling between the lithium tantalate single crystals (LT) or between the lithium niobate single crystals (LN) during the production process of the composite wafer or the production process of the surface acoustic wave (SAW) device is suppressed, and desired surface acoustic wave (SAW) device performance can be obtained.

[0013] The heat treatment is preferably performed on the composite wafer that has been bonded at room temperature at 200°C to 250°C for at least 60 minutes, or at 150°C for at least 120 minutes. While the bonding between lithium tantalate single crystals or lithium niobate single crystals of different orientations achieves sufficient bonding strength, the influence of warpage during and after heat treatment can be suppressed.

[0014] Further, in the wafer after the room-temperature bonding, a lithium tantalate single crystal or lithium niobate single crystal of the different orientations, a SiO₂ layer, an amorphous Si layer, and a polycrystalline Si layer may be laminated in this order from the surface side on a Si substrate serving as a support wafer, and after the heat treatment, the lithium tantalate single crystal or the lithium niobate single crystal on the outermost surface may be polished to be thinned. Further, in the wafer after the room-temperature bonding, a first Si substrate, a lithium tantalate single crystal or lithium niobate single crystal of the different orientations, a SiO₂ layer, an amorphous Si layer, and a polycrystalline Si layer may be laminated in this order from the surface side on a second Si substrate serving as a support wafer, and after the heat treatment, the first Si substrate on the outermost surface may be removed, and film thickness adjustment polishing of the lithium tantalate single crystal or the lithium niobate single crystal may be performed. As described above, after the heat treatment, the lithium tantalate single crystal or the lithium niobate single crystal on the outermost surface may be polished to be thinned, or after the heat treatment, the first Si substrate on the outermost surface may be removed, and film thickness adjustment polishing of the lithium tantalate single crystal or the lithium niobate single crystal may be performed. The present invention can be applied to any of the manufacturing flows.

Effects of the Invention

[0015] According to each aspect of the present invention, even when lithium tantalate single crystal wafers (LT) of different orientations are bonded to each other, or even when lithium niobate single crystal wafers (LN) of different orientations are bonded to each other, a composite wafer and a method for manufacturing the composite wafer that have sufficient bonding strength without peeling can be obtained. In this way, peeling between the lithium tantalate single crystal wafers (LT) or between the lithium niobate single crystal wafers (LN) is suppressed, and when these composite wafers are used for surface acoustic wave (SAW) devices, desired performance can be obtained. [Brief explanation of the drawing]

[0016] [Figure 1] Figure 1 shows the experimental results of bonding strength after bonding LT wafers together and LN wafers together at room temperature. [Figure 2] Figure 2 shows experimental results of bonding strength when LT wafers and LN wafers are bonded at room temperature and then heat-treated. [Figure 3] Figure 3 shows the bond interface structure before heat treatment, with (b) being an enlarged view of (a). [Figure 4] Figure 4 shows the bond interface structure after heat treatment, with (b) being an enlarged view of (a). [Figure 5] Figure 5 shows the manufacturing flow of the first composite wafer. [Figure 6] Figure 6 shows the manufacturing flow of the two composite wafers. [Modes for carrying out the invention]

[0017] The present invention provides a method for manufacturing a composite wafer, characterized by bonding lithium tantalate single crystals or lithium niobate single crystals of different orientations at room temperature, followed by further heat treatment at a temperature of 250°C or lower. This invention is based on the premise of bonding lithium tantalate single crystals or lithium niobate single crystals with different orientations at room temperature, and is premised on the fact that this room temperature bonding cannot suppress delamination between lithium tantalate single crystals or lithium niobate single crystals, and therefore does not have sufficient bonding strength. Therefore, the inventors first verified the bonding strength after bonding at room temperature.

[0018] [Bond strength after room temperature bonding] When activating a junction by irradiating it with a fast atomic beam (FAB) in a high vacuum environment, it is known that the energy and irradiation dose of the fast atomic beam (FAB) affect the junction strength. Therefore, we experimentally investigated the bonding strength between lithium tantalate single crystal wafers (LT) or lithium niobate single crystal wafers (LN) with different orientations by setting the energy and irradiation dose to three levels each (low, medium, and high).

[0019] First, the lithium tantalate single crystal wafers (LT) or lithium niobate single crystal film wafers (LN) with different orientations used in this bonding strength experiment were obtained as follows.

[0020] Single-crystal lithium tantalate and lithium niobate single-crystal ingots manufactured by the CZ method were processed into 42°YX and 128°YX wafers, respectively. These LT and LN wafers had a diameter of 6 inches and a thickness of 350 μm. To minimize the influence of the smoothness of the bonding surface on the bonding strength, the surface roughness Ra of the bonding surface (front side) was polished to 0.2 nm or less. The prepared wafers were both oriented in the same direction, but when bonding LT wafers together and LN wafers together at room temperature, one wafer was inverted using the orientation flat as a reference. This effectively bonded wafers with different orientations. A commercially available room-temperature bonding apparatus (BOND MEISTER, manufactured by NIDEK Machine Tools Co., Ltd.) was used to bond the prepared wafers.

[0021] Furthermore, a low FAB energy during joining refers to an acceleration voltage of 1.2kV for the FAB gun, a medium FAB energy refers to 1.5kV, and a high FAB energy refers to 1.8kV. The current value of the FAB gun was set to 100mA in all cases. Additionally, a low FAB irradiation dose refers to an irradiation time of 60 seconds, a medium FAB irradiation dose refers to an irradiation time of 120 seconds, and a high FAB irradiation dose refers to an irradiation time of 180 seconds.

[0022] To account for variations in experiments and measurements, three sets of wafers were bonded under each condition, and the bonding strength was measured at four locations on the outer edge of each bonded wafer.

[0023] [Method for evaluating joint strength] The bonding strength was evaluated using a general crack opening method. This method involves inserting a blade into the edge face of the bonded wafer and measuring the distance of delamination to assess the bonding strength. The formula for calculating the bonding strength is as follows: γ=3h 2 Et 3 / 32L 4 Here, γ: bonding strength, h: blade thickness, E: wafer Young's modulus, t: wafer thickness, and L: delamination distance. The calculations were performed assuming the Young's modulus of the single-crystal wafer was 230 GPa and 170 GPa for LT and LN, respectively. Note that if the bonding strength is sufficiently high, the wafer may break when inserting the blade. In this case, the bonding strength cannot be calculated, so it was assumed to be 2 J / m 2 This is shown in Figure 2.

[0024] During measurement, the bonding strength varied relatively large and also changed depending on the position between wafers and within the wafer surface. Therefore, three wafers bonded under each condition were prepared, and measurements were taken at four locations on each wafer to determine the maximum, minimum, and average bonding strength. The results are shown in Figure 1.

[0025] As a result, as shown in Figure 1, it was confirmed that the bonding strength changes depending on the FAB energy and FAB irradiation dose, but conditions for obtaining sufficient bonding strength could not be found. Furthermore, to suppress delamination and other issues, the bonding strength should be at least 1.5 J / m 2 A certain level of joint strength is required, and in particular, a minimum joint strength is important. In other words, a joint strength of 1.5 J / m is required in some areas. 2 It's not enough to simply meet the above criteria; the minimum joint strength must be 1.5 J / m 2 It must be at least that much. In other words, as can be seen in Figure 1, the minimum joint strength is 1.5 J / m 2 The above findings indicate that it is not possible to bond lithium tantalate single crystals (LT) with different orientations, or lithium niobate single crystals (LN), with sufficient strength across the entire wafer surface using only room-temperature bonding.

[0026] As shown in Figure 1, when the FAB energy is low and the FAB irradiation dose is low, and when the FAB energy is high or the FAB irradiation dose is high, the bonding strength tends to decrease, and the variation in bonding strength depending on the wafer site also tends to increase. When the FAB energy is low and the FAB irradiation dose is low, the surface activation treatment is insufficient, and it is considered that sites where the activation treatment is significantly insufficient occur within the wafer surface. When the energy is high or the FAB irradiation dose is high, the activation treatment is sufficient, but the irradiation damage increases, the surface roughness of the bonding surface increases, and this is considered to be the result of the non-uniform contact surface during bonding. In addition, although the bonding strength is highest under the optimal conditions for both energy and irradiation dose, in any case, 1.5J / m 2 The above sufficient bonding strength was not obtained.

[0027] [Bonding strength when heat treatment is performed after room temperature bonding] A heat treatment was added after room temperature bonding to investigate the change in bonding strength. The heat treatment was performed on bonded wafers having a bonding strength of at least 0.4J / m after room temperature bonding 2 The heat treatment was carried out by holding the wafers at 100°C to 300°C for 60 minutes to 780 minutes. The bonding strength after room temperature bonding is 0.4J / m 2 The reason why wafers satisfying the above conditions were selected as targets is that preliminary experiments confirmed that the frequency of peeling progressing due to warpage during heat treatment is high, which is not suitable for the purpose of this experiment. Specifically, under the bonding conditions in the aforementioned bonding experiment, bonding was performed under conditions where the combinations of FAB energy and FAB irradiation dose were low and medium, medium and low, and medium and medium, and the bonding strength after room temperature bonding was at least 0.4J / m 2 The wafers satisfying the above conditions were used as targets. In consideration of variations in experiments and measurements, three sets of bonded wafers under the same conditions were used, and the bonding strength at four locations on each wafer was measured.

[0028] Furthermore, the bonding strength after room-temperature bonding must be at least 0.4 J / m 2 The bonded wafer was subjected to a heat treatment, held at 100°C to 300°C for 60 to 780 minutes. The heating rate from room temperature to the holding temperature and the cooling rate were set at 20°C / min. The joint strength after heat treatment was investigated. As a result, as shown in Figure 2, if the heat treatment temperature is 200°C or higher, a minimum of 1.5 J / m³ is obtained after holding for 60 minutes. 2 It was found that sufficient joint strength could be obtained.

[0029] Furthermore, the change in bond strength as the holding time increased at holding temperatures of 100°C and 150°C was investigated. As a result, even when held for up to 13 hours at 100°C, the minimum bond strength was 1.5 J / m 2 It does not reach that level, but if held at 150°C for more than 2 hours, it reaches 1.5 J / m³. 2 It was found that this is the case.

[0030] Thus, while higher heat treatment temperatures increase joint strength, lower heat treatment temperatures are preferable for the following reasons. Firstly, there is a risk that the polarization will change from monopolar to multipolar if the temperature is not below the Curie temperature. Secondly, due to the anisotropy of the coefficient of thermal expansion, warping will increase during and after heat treatment, which may prevent the manufacture of composite wafers. Therefore, it is desirable that the heat treatment temperature be 250°C or lower, and more preferably 150°C or lower.

[0031] Thus, in bonding lithium tantalate single crystals (LT) with different orientations and lithium niobate single crystals (LN) with different orientations, the bonding strength across the entire wafer is 1.5 J / m². 2 To obtain the above results, it was found that heat treatment at 150°C for 2 hours or more, or at 200°C to 250°C or higher for 60 minutes or more, should be performed after room temperature bonding.

[0032] [Joint interface structure before and after heat treatment] We clarified the conditions under which sufficient joint strength can be obtained by adding heat treatment after room-temperature bonding. The relationship between the change in joint strength and the change in interface structure before and after this heat treatment was investigated using cross-sectional TEM analysis.

[0033] Examples of cross-sectional TEM analysis results are shown in Figures 3 and 4. Figure 3 shows that two 128Y-X LN wafers were bonded at room temperature under low and medium FAB energy and FAB irradiation conditions, respectively, with a minimum bonding strength of 0.4 J / m². 2 Figure 4 is a cross-sectional TEM image of the vicinity of the bonding interface of the bonded wafer.

[0034] Comparing Figure 3 and Figure 4, the following three points highlight significant changes in the interface structure due to heat treatment. Firstly, the bright, white, linear bands on the bonding surface thin out due to heat treatment. Secondly, after heat treatment, a dark, contrasting band with poor crystallinity (a mixture of single crystal and amorphous material) is formed at the boundary between the amorphous layer and the single crystal adjacent to the bonding surface. The thickness of the altered layer (the non-single crystal layer and the layer containing a mixture of single crystal and amorphous material) across this bonding surface ranges from 2.7 nm after room-temperature bonding to a bonding strength of 1.5 J / m². 2 After the heat treatment described above, the contrast increased from 4 nm to 5 nm. Thirdly, focusing on the low-magnification cross-sectional TEM images in Figures 3 and 4, it can be seen that before heat treatment, there are intermittent changes in contrast in the direction parallel to the joint surface across the joint surface, but after heat treatment, these have almost completely disappeared. These findings clearly indicate that atoms near the bonding surface were rearranged to become energetically stable through heat treatment. In other words, it shows that before bonding, there was a large variation in residual stress near the bonding surface, and after heat treatment, this residual stress was relieved.

[0035] In particular, when the thickness of the altered layer at the interface reaches 2.7 nm after room-temperature bonding, the bonding strength is 1.5 J / m 2Considering that the thickness increased from 4 nm to 5 nm after the heat treatment described above, if the thickness of the incomplete single crystal layer containing amorphous material formed at the bonding interface is between 4 nm and 5 nm as observed by cross-sectional TEM, then the bonding strength is 1.5 J / m 2 It can be seen that this is the case.

[0036] Although increasing the heat treatment time may further increase the thickness of the altered layer, this increases productivity. In addition, by the time the altered layer is 4 nm to 5 nm thick, the contrast caused by strain has already been significantly reduced, so further stress relaxation at the bonding interface is unnecessary. Furthermore, when the altered layer is thinner than 4 nm, the residual stress at the bonding interface is not sufficiently relaxed, and the effect of heat treatment on improving bonding strength is not fully obtained.

[0037] [Manufacturing of composite wafers] The structure of a composite wafer, which includes a structure in which lithium tantalate single crystals (LT) and lithium niobate single crystals (LN) with different orientations are joined together, is as shown in Figure 5(h) and Figure 6(j), for example, a first lithium tantalate single crystal film (LT-1) 1, a second lithium tantalate single crystal film (LT-2) 2, an SiO2 layer 3, an amorphous Si layer 4, a polycrystalline Si layer 5, and a Si substrate 6 from the surface side. To manufacture such a composite wafer structure, it is not enough for lithium tantalate single crystals (wafers) with different orientations to be bonded together with sufficient strength. It is also necessary to verify that delamination, warping, and wafer cracking do not occur, including the thinning of the lithium tantalate single crystals (wafers) and methods of integrating them with other layers.

[0038] In the verification of the present invention, it was confirmed that composite wafers can be manufactured using the two flow diagrams shown in Figures 5 and 6. The flow chart shown in Figure 5 illustrates a method in which the outermost surface of the first lithium tantalate single crystal wafer (LT-1) is thinned and polished after heat treatment. Figure 5(a) shows the process of depositing a polycrystalline Si layer 5 onto a Si substrate 6, which is a support substrate. Specifically, a polycrystalline Si layer 5 with a thickness of 1,050 nm to 1,200 nm is deposited on the Si substrate 6 by CVD. Figure 5(b) shows the process of polishing the bonding surface of the polycrystalline Si layer 5 deposited on the Si substrate 6. Specifically, the polycrystalline Si layer on the Si substrate is polished to a thickness of 1,000 nm ± 50 nm by the CMP method to reduce surface roughness. Figure 5(c) shows the process of depositing SiO23 and amorphous Si4 on the second lithium tantalate single crystal wafer 2. Specifically, SiO23 is deposited on the second lithium tantalate single crystal wafer 2 by sputtering, and then amorphous Si4 is deposited continuously using the same deposition apparatus. Figure 5(d) shows the process of polishing the amorphous Si4 film deposited on the second lithium tantalate single crystal wafer. Specifically, the surface of the amorphous Si4 that will form the bonding surface is smoothed to an Ra of approximately 0.2 nm by CMP.

[0039] Figure 5(e) shows the bonding of the polycrystalline Si layer 5 of the Si substrate 6 obtained in Figure 5(b) with the amorphous Si4 obtained in Figure 5(d) at room temperature. Since this room-temperature bonding involves a Si-to-Si junction, there are already many practical examples, and the general Si-to-Si bonding conditions are sufficient. Figure 5(f) shows the process of polishing the second lithium tantalate single crystal wafer 2. Specifically, the second lithium tantalate single crystal wafer 2 is thinned to a desired thickness by grinding and polishing. The thickness is, for example, 300 nm to 350 nm. If uniformity of the in-plane thickness of the second lithium tantalate single crystal 2 is important, it is desirable to also apply the ion trimming method to adjust the film thickness. Figure 5(g) shows the room-temperature bonding of the second lithium tantalate single crystal film 2 obtained in Figure 6(f) with the first lithium tantalate single crystal wafer 1. As mentioned earlier, the conditions for this room-temperature bonding are a minimum bonding strength of 0.4 J / m 2 Select the joining conditions that meet the above criteria. Furthermore, to ensure sufficient bonding strength between lithium tantalate single crystal films (wafers) (LT), the heat treatment conditions after room-temperature bonding were determined to be 1.5 J / m based on the aforementioned experiments. 2 To obtain the above-mentioned bonding strength, we verified the results using four conditions: 150°C for 120 minutes, 200°C for 60 minutes, 250°C for 60 minutes, and 300°C for 60 minutes. Figure 5(h) shows the process of thinning the first lithium tantalate single crystal wafer 1 to a desired thickness by grinding and polishing. Specifically, the first lithium tantalate single crystal wafer 1 is thinned by grinding and polishing until it reaches a thickness of 300 nm to 400 nm. If uniformity of the in-plane thickness of the first lithium tantalate single crystal 1 is important, it is desirable to also apply the ion trimming method to adjust the film thickness.

[0040] In this way, the composite wafers obtained through each step in Figure 5 were examined for delamination and cracking. Similarly, the same steps as in Figures 5(a) to (h) were used to examine the delamination and cracking of composite wafers obtained by bonding lithium niobate single crystal films (wafers) (LN) together.

[0041] Next, based on the flow shown in Figure 6, a method is described in which the outermost first Si substrate is removed after heat treatment, and the thickness of the first lithium tantalate single crystal film (wafer) (LT-1) is adjusted by polishing. Figure 6(a) shows the process of depositing SiO23 and amorphous Si4 on the second lithium tantalate single crystal wafer 2. Specifically, SiO23 is deposited on the second lithium tantalate single crystal wafer 2 by sputtering, and then amorphous Si4 is deposited continuously using the same deposition apparatus. Figure 6(b) shows the process of polishing the amorphous Si film deposited on the second lithium tantalate single crystal wafer. Specifically, the surface of the amorphous Si4 that will form the bonding surface is smoothed to an Ra of approximately 0.2 nm by CMP. Figure 6(c) shows the process of depositing a polycrystalline Si layer 5 onto a Si substrate 6, which is a support substrate. Specifically, a polycrystalline Si layer 5 with a thickness of 1,100 nm to 1,200 nm is deposited on the Si substrate 6 by CVD. Figure 6(d) shows the process of polishing the bonding surface of the polycrystalline Si layer 5 deposited on the Si substrate 6. Specifically, the polycrystalline Si layer on the Si substrate is polished to a thickness of 1,000 nm ± 50 nm by the CMP method to reduce surface roughness. Figure 6(e) shows the bonding of the polycrystalline Si layer 5 of the Si substrate 6 obtained in Figure 6(d) with the amorphous Si 4 obtained in Figure 6(b) at room temperature. Under these conditions for room-temperature bonding, the result is a Si-to-Si bond, and there are already many practical examples; therefore, the general Si-to-Si bonding conditions are sufficient.

[0042] Figure 6(f) shows the process of grinding and polishing the second lithium tantalate single crystal wafer 2. Specifically, the second lithium tantalate single crystal wafer 2 is thinned to a desired thickness, for example, 300 nm to 350 nm. If uniformity of the in-plane thickness of the second lithium tantalate single crystal 2 is important, it is desirable to also apply the ion trimming method to adjust the film thickness. Figure 6(g) shows the process of bonding a first lithium tantalate single crystal wafer and a Si substrate at room temperature. The conditions for this room-temperature bonding can be the same as those for bonding Si to Si, but modifications are also possible. Specifically, in the surface activation treatment by FAB, in addition to activating and pressing the bonding surfaces of both materials, irradiating only the Si substrate side with FAB can be effective in terms of bonding strength by coating the surface of the first lithium tantalate single crystal wafer with Si atoms sputtered from the surface layer of the Si substrate. In other words, Si to Si will be bonded during the pressing process. Figure 6(h) shows the process of thinning the first lithium tantalate single crystal wafer on the Si substrate 6 and polishing the bonding surface. Specifically, the first lithium tantalate single crystal wafer is thinned to a thickness of 400 nm to 500 nm by grinding and polishing. If uniformity of the in-plane thickness of the first lithium tantalate single crystal 1 is important, it is desirable to also apply the ion trimming method to adjust the film thickness. Figure 6(i) shows the room-temperature bonding of the second lithium tantalate single crystal film 2 obtained in Figure 6(f) and the first lithium tantalate single crystal film 1 obtained in Figure 6(h). As mentioned earlier, the conditions for this room-temperature bonding are a minimum bonding strength of 0.4 J / m 2 Select the joining conditions that meet the above criteria. Furthermore, to ensure sufficient bonding strength between lithium tantalate single crystal films (LT), the heat treatment conditions after room-temperature bonding were verified using four conditions: 150°C for 120 minutes, 200°C for 60 minutes, 250°C for 60 minutes, and 300°C for 60 minutes. Figure 6(j) shows the process of polishing the first lithium tantalate single crystal film 1 after removing the outermost Si substrate. Specifically, the Si substrate is removed by grinding and etching, exposing the first lithium tantalate single crystal film 1 to the surface, and then polished until its thickness reaches 250 nm to 300 nm. If uniformity of the in-plane thickness of the first lithium tantalate single crystal 1 is important, it is desirable to also apply ion trimming to adjust the film thickness.

[0043] In this way, the composite wafers obtained by each process in Figure 6 were examined for delamination and cracking. Similarly, the same processes as in Figures 6(a) to (h) were applied to lithium niobate single crystal wafers (LN), and the composite wafers formed by bonding lithium niobate single crystal wafers (LN) together were examined for delamination and cracking.

[0044] In both flow diagrams shown in Figures 5 and 6, heat treatment at temperatures above 300°C sometimes resulted in delamination of the lithium tantalate single crystal (LT) or lithium niobate single crystal (LN), or cracking including the Si substrate. Furthermore, delamination sometimes occurred even at a heat treatment temperature of 250°C. This is thought to be due to increased warping caused by the difference in thermal expansion coefficients of the two substrates being bonded, resulting from the temperature change during heat treatment. Therefore, it was found that the heat treatment must be performed at 250°C or lower to manufacture a composite wafer with the desired structure. [Explanation of Symbols]

[0045] 1. First lithium tantalate single crystal film (wafer) 2. Second lithium tantalate single crystal film (wafer) 3 SiO2 layer 4 Amorphous Si layer 5 Polycrystalline Si layer 6 Si substrate

Claims

1. In a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystals of different orientations are stacked, A composite wafer characterized in that the thickness of the incomplete single crystal layer containing amorphous material formed at the bonding interface between the lithium tantalate single crystal or the lithium niobate single crystal is 4 nm or more and 5 nm or less.

2. From the surface side, stacking of the lithium tantalate single crystal or the lithium niobate single crystal of the different orientations, SiO 2 The composite wafer according to claim 1, characterized in that it is laminated with a layer, an amorphous Si layer, a polycrystalline Si layer, and a Si substrate.

3. In a method for manufacturing a composite wafer having a structure in which lithium tantalate single crystals or lithium niobate single crystal films of different orientations are directly bonded, A process for forming lithium tantalate single crystals or lithium niobate single crystals with different orientations, A step of bonding the lithium tantalate single crystals or lithium niobate single crystals formed with different orientations at room temperature, A method for manufacturing a composite wafer, further characterized by including a heat treatment step of 250°C or lower after the room temperature bonding step.

4. The method for manufacturing a composite wafer according to claim 3, characterized in that the heat treatment is performed by heat-treating the room-temperature bonded composite wafer at a temperature between 200°C and 250°C for at least 60 minutes or at 150°C for at least 120 minutes.

5. The wafer after room-temperature bonding has a Si substrate as a support wafer, with layers of lithium tantalate single crystals or lithium niobate single crystals of different orientations stacked from the surface side, SiO 2 A layer, an amorphous Si layer, and a polycrystalline Si layer are stacked, The method for manufacturing a composite wafer according to claim 3, wherein, after the heat treatment, the lithium tantalate single crystal or the lithium niobate single crystal on the outermost surface is polished to form a thin film.

6. The wafer after room-temperature bonding has a second Si substrate as a support wafer, a first Si substrate on the surface side, and stacked lithium tantalate single crystals or lithium niobate single crystals of different orientations, SiO 2 A layer, an amorphous Si layer, and a polycrystalline Si layer are stacked, The method for manufacturing a composite wafer according to claim 3, wherein, after the heat treatment, the outermost surface of the first Si substrate is removed and the lithium tantalate single crystal or the lithium niobate single crystal is polished to adjust the film thickness.

Citation Information

Patent Citations

  • Elastic wave device

    JP2024067557A